Conformational alterations in the CD4 binding cavity of HIV-1 gp120 influencing gp120-CD4 interactions and fusogenicity of HIV-1 envelopes derived from brain and other tissues - Gray, L.; Sterjovski, J.; Ramsland, Paul; Churchill, M.; Gorry, P. (2011)
Background: CD4-binding site (CD4bs) alterations in gp120 contribute to HIV-1 envelope (Env) mediated fusogenicity and the ability of gp120 to utilize low levels of cell-surface CD4. In a recent study, we constructed three-dimensional models of gp120 to illustrate CD4bs conformations associated with enhanced fusogenicity and enhanced CD4-usage of a modestly-sized panel of blood-derived HIV-1 Envs (n = 16). These conformations were characterized by a wider aperture of the CD4bs cavity, as constrained by the inner-most atoms at the gp120 V1V2 stem and the V5 loop. Here, we sought to provide further validation of the utility of these models for understanding mechanisms that influence Env function, by characterizing the structure-function relationships of a larger panel of Envs derived from brain and other tissues (n = 81). Findings: Three-dimensional models of gp120 were generated by our recently validated homology modelling protocol. Analysis of predicted CD4bs structures showed correlations between the aperture width of the CD4bs cavity and ability of the Envs to mediate cell-cell fusion, scavenge low-levels of cell-surface CD4, bind directly to soluble CD4, and bind to the Env mAb IgG1b12 whose epitope overlaps the gp120 CD4bs. These structural alterations in the CD4bs cavity were associated with repositioning of the V5 loop. Conclusions: Using a large, independent panel of Envs, we can confirm the utility of three-dimensional gp120 structural models for illustrating CD4bs alterations that can affect Env function. Furthermore, we now provide new evidence that these CD4bs alterations augment the ability of gp120 to interact with CD4 by increasing the exposure of the CD4bs.